Ingenious ambient temperature fabrication zirconium-metal organic framework laden polysaccharide aerogel as an efficient glyphosate scavenger. Issue 6 (December 2021) - Luo, Xueli; Huang, Gengli; Chen, Xiaokai; Guo, Jie; Yang, Weixia; Tang, Wenzhi; Yue, Tianli; Li, Zhonghong
Abstract: Developing superior adsorbents to remove pollutants from aqueous solution is increasingly becoming urgent with respect to grave water pollution and public health consequences. Herein, a metal organic framework (MOFs)-decorated shapeable aerogel (CS-CNC@UiO-66-NH2 ) prepared by in situ growth of Zr-MOF (UiO-66-NH2 ) on chitosan/cellulose nanocrystal (CS-CNC) hybrid aerogel at room temperature was developed to remove glyphosate (Gly) from water. The aerogel possessed highly porous structure and excellent water stability upon introduction of cellulose nanocrystals extracted from cotton. Besides, the loading ratio of UiO-66-NH2 of the proposed ambient growth strategy (37.72%) was higher than conventional solvothermal method (10.91%) because of the structure integrity of polysaccharide aerogels at room temperature. Further, the BET area and porosity of CS-CNC@UiO-66-NH2 aerogel increased from 21.65 m 2 g −1 to 231.60 m 2 g −1 and 87.47–93.03% due to the synergy of UiO-66-NH2. Owing to these virtues, the separation-free aerogel exhibited a high adsorption capacity of 133.7 mg/g in batch adsorption and displayed high recyclability over four consecutive adsorption-desorption cycles. Moreover, the Zr-OH/oxygen-containing moieties of the aerogel, electrostatic attraction and hydrogen-bonding accounted for driving Gly adsorption. Considering practical application, the aerogels were packed in glass column for fixed-bed test which revealed that the aerogels could decontaminate Gly with column adsorption capacity of 44.99 mg/g. Consequently, the CS-CNC@UiO-66-NH2 aerogel with highly porous structure exhibited good Gly adsorption and simple separation, offering a novel strategy to synchronously improve adsorption capacity of polysaccharide-based adsorbent and MOFs shaping for pollutant removal. Graphical Abstract: ga1 Highlights: Synchronously improving adsorption of polysaccharide adsorbent and shaping of MOFs. High UiO-66-NH2 loading polysaccharide aerogel prepared by ambient growth. Cellulose nanocrystal endowed highly porous structure and enhanced water stability. Enhanced adsorption due to porous structure of aerogel and high porosity of MOFs. Facile separation and recyclability of the aerogel adsorbent after adsorption.